Novel Ir(III)-based Triplet Photosensitisers For Triplet-Triplet Annihilation Upconversion - CAVERLY, COLIN SE?N (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
Chapter 1 contains introduction to the topic of triplet-triplet annihilation upconversion (TTA-UC), including the process of upconversion, the properties of efficient photosensitiser (PS) molecules and the other uses that these PS molecules may have. Also included is a brief literature review regarding the development of various PS molecules for upconversion. This chapter also covers the aims of the thesis, and the synthetic background used to create the novel Ir(III)-based PS molecules within. Chapter 2 covers the synthesis of each complex, the difficulties encountered, and the attempts taken to circumvent these. Also covered is the structural characterisation of each complex using nuclear magnetic resonance (NMR) and mass spectrometry (MS). Chapter 3 covers the photophysical investigations of Ir1 - Ir4, including UV-vis absorption, emission, singlet oxygen sensitisation, transient absorption, quenching and TTA-UC measurements. Also, the cyclic voltammetry measurements of Ir1- Ir4 are described. Lastly, the extensive results of density functional theory (DFT) calculations into Ir1 - Ir4, and comparison of the calculated values to the experimentally determined analogues are detailed. Similarly to Chapter 3, Chapter 4 covers the photophysical, cyclic voltammetric and DFT investigations into the dinuclear Ir5 and Ir6. Chapter 5 gives a detailed account of each successful reaction carried out, including reagents, solvents, molar details, purification details and yields. The NMR, IR and melting point data of each product is also given here.
APPROVED
Keywords: Upconversion; Iridium; Photophysics; Photochemistry; Energy; Photocatalysis; Triplet-triplet annihilation upconversion